The Implementation of E-CRM In Improving Marketing In Delvi Jilbab - Uswatun Hasanah; Rolly Yesputra; Afrisawati Afrisawati (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
Delvi Jilbab is one of the shop businesses engaged in selling hijab. The obstacles that occur in Delvi Jilbab are the lack of promotion, the absence of a customer data management system, customers have difficulty in finding out information about marketing at Delvi Jilbab. Based on the data obtained, it can be seen that the customer development at Delvi Jilbab has decreased in the last two months. This shows the need for a system in order to maintain and increase customer loyalty. The concept of E-CRM aims to increase loyalty and provide satisfaction to customers. Therefore we need an information system by implementing E-CRM that can assist customers in finding out information about products without coming directly to the Delvi Jilbab store, and assisting Delvi Jilbab in managing customer data. System design using UML diagrams and implementation using PHP and MySQL. The results showed that the application of E-CRM can increase customer loyalty and improve marketing at Delvi Jilbab with the E-CRM system that can facilitate customers in obtaining information and assist Delvi Jilbab in managing customer transaction data. Keywords: Delvi Hijab, E-CRM, PHP, MySQL.